Electrical Modelling and Investigation of Laser Beam Welded Joints for Lithium-Ion Batteries - Sören Hollatz; Sebastian Kremer; Cem Ünlübayir; Dirk Uwe Sauer; Alexander Olowinsky; Arnold Gillner (Batteries, 2020)
The growing electrification of vehicles and tools increases the demand for low resistance contacts. Today’s batteries for electric vehicles consist of large quantities of single battery cells to reach the desired nominal voltage and energy. Each single cell needs a contacting of its cell terminals, which raises the necessity of an automated contacting process with low joint resistances to reduce the energy loss in the cell transitions. A capable joining process suitable for highly electrically conductive materials like copper or aluminium is the laser beam welding. This study contains the theoretical examination of the joint resistance and a simulation of the current flow dependent on the contacting welds’ position in an overlap configuration. The results are verified by examinations of laser-welded joints in a test bench environment. The investigations are analysing the influence of the shape and position of the weld seams as well as the influence of the laser welding parameters. The investigation identifies a tendency for current to flow predominantly through a contact’s edges. The use of a double weld seam with the largest possible distance greatly increases the joint’s conductivity, by leveraging this tendency and implementing a parallel connection. A simplistic increase of welded contact area does not only have a significantly smaller effect on the overall conductivity, but can eventually also reduce it.